Mutation of Signal Transducer and Activator of Transcription 5 (STAT5) Binding Sites Decreases Milk Allergen αS1-Casein Content in Goat Mammary Epithelial Cells - Ning Song; Jun Luo; Lian Huang; Saige Zang; Qiuya He; Jiao Wu; Jiangtao Huang (Foods, 2022)
αS1-Casein (encoded by the CSN1S1 gene) is associated with food allergy more than other milk protein components. Milk allergy caused by αS1-casein is derived from cow milk, goat milk and other ruminant milk. However, little is known about the transcription regulation of αS1-casein synthesis in dairy goats. This study aimed to investigate the regulatory roles of signal transducer and activator of transcription 5 (STAT5) on αS1-casein in goat mammary epithelial cells (GMEC). Deletion analysis showed that the core promoter region of CSN1S1 was located at −110 to −18 bp upstream of transcription start site, which contained two putative STAT5 binding sites (gamma-interferon activation site, GAS). Overexpression of STAT5a gene upregulated the mRNA level and the promoter activity of the CSN1S1 gene, and STAT5 inhibitor decreased phosphorylated STAT5 in the nucleus and CSN1S1 transcription activity. Further, GAS site-directed mutagenesis and chromatin immunoprecipitation (ChIP) assays revealed that GAS1 and GAS2 sites in the CSN1S1 promoter core region were binding sites of STAT5. Taken together, STAT5 directly regulates CSN1S1 transcription by GAS1 and GAS2 sites in GMEC, and the mutation of STAT5 binding sites could downregulate CSN1S1 expression and decrease αS1-casein synthesis, which provide the novel strategy for reducing the allergic potential of goat milk and improving milk quality in ruminants.